Smart objects and technologies for social good : second International Conference, GOODTECHS 2016, Venice, Italy, November 30-December 1, 2016, Proceedings /: second International Conference, GOODTECHS 2016, Venice, Italy, November 30-December 1, 2016, Proceedings. (2017) - Unknown
No abstract available